2017
DOI: 10.1111/jfpp.13302
|View full text |Cite
|
Sign up to set email alerts
|

Changes in enzymatic activities during “koji” incubation and natural fermentation of soybean paste

Abstract: Soybean paste production requires two steps “koji” incubation and natural fermentation. During the incubation of the koji, the protease activity was gradually increased and the highest activity was obtained on 30th day. Neutral protease was the predominant protease and it was significantly increased during the incubation of the koji. The nitrogen solubility index, nonprotein nitrogen (NPN), aminophenol nitrogen, and peptides concentration were gradually increased and they were 69.07%, 42.07%, 3.73%, and 38.34%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The soluble dietary fibers (SDF) and insoluble dietary fibers (IDF) contents were determined according to the gravimetric enzymatic method as previously described by Prosky et al [7]. Protein content (N×6.25) was estimated by the Kjeldahl digestion method followed by spectrophotometric determination of the resulting ammonia according to the method reported by Elfalleh et al [8]. Total carbohydrates were evaluated by the phenol sulphuric acid method [9], after hot digestion with 1.5 M sulphuric acid.…”
Section: Chemical Analysis and Functional Characteristics Of Z Lotusmentioning
confidence: 99%
“…The soluble dietary fibers (SDF) and insoluble dietary fibers (IDF) contents were determined according to the gravimetric enzymatic method as previously described by Prosky et al [7]. Protein content (N×6.25) was estimated by the Kjeldahl digestion method followed by spectrophotometric determination of the resulting ammonia according to the method reported by Elfalleh et al [8]. Total carbohydrates were evaluated by the phenol sulphuric acid method [9], after hot digestion with 1.5 M sulphuric acid.…”
Section: Chemical Analysis and Functional Characteristics Of Z Lotusmentioning
confidence: 99%
“…Meanwhile, Azad Shah, Tokunaga, Kurihara, and Takahashi () reported that lipolysis and lipid oxidation are responsible for the thickness, mouthfulness, and continuity taste in migaki‐nishin, a dried fish product. To date, published studies have focused on proteins (Chou & Ling, ; Kaewkrod, Niamsiri, Likitwattanasade, & Lertsiri, ; Yong & Wood, ) and starch (Elfalleh, Sun, He, Kong, & Ma, ; Liu, Chen, Fan, Huang, & Han, ) degradation and umami peptides (Kim et al., ; Zhuang et al., ) of soy sauce. And the changes of lipid and its relationship with volatile compounds have been investigated during the koji fermentation of soy sauce (Feng et al., , ; Gao et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that grass pea misos have a higher starch content than soybean misos may lead to a greater impact of degradation over time. The proteolytic enzymatic action of koji 43 may have contributed to the availability of non‐digestible starch for degradation, promoting a faster kinetic of maturation. However, soybean misos G ' 1 Hz values were the first to stabilize (after 90 and 60 days for salty and sweet miso, respectively), indicating an earlier matured state as was observed by the apparent colour evolution of misos (Fig.…”
Section: Resultsmentioning
confidence: 99%